Global research landscape of blue accounting: Bibliometric insights from 2015 to 2025 - Izza Maulida Santoso; Nurmala Nurmala; Destia Pentiana; Muhammad Syahrial (Indonesia Auditing Research Journal, 2026)
The Blue Economy has gained global attention as a framework for balancing marine resource utilization with environmental sustainability. Supporting this transition requires effective systems to measure and report ocean-related natural capital, leading to the emergence of Blue Accounting as an integrative approach linking accounting practices, sustainability governance, and policy decision-making. This study examines the development of Blue Accounting research between 2015 and 2025 using a bibliometric approach combined with qualitative synthesis. The findings indicate a gradual evolution of the field, beginning with conceptual discussions of the blue economy, followed by growing attention to environmental valuation, ocean accounting integration, and blue carbon assessment. More recent studies emphasize operational applications, including policy implementation and cumulative impact accounting. Although publication growth remains moderate, research trends show increasing interdisciplinary collaboration and policy relevance. Key challenges include institutional coordination and the lack of standardized accounting frameworks. Overall, Blue Accounting is evolving into a strategic tool that supports sustainable ocean governance by integrating ecological and economic perspectives, contributing to more transparent decision-making and advancing the objectives of sustainable marine development.